Comprehensive meta-analysis of resilience interventions. (December 2020) - Liu, Jenny J.W.; Ein, Natalie; Gervasio, Julia; Battaion, Mira; Reed, Maureen; Vickers, Kristin
Abstract: Background/Rationale: There is no current consensus on operational definitions of resilience. Instead, researchers often debate the optimal approach to understanding resilience, while continuing to explore ways to enhance and/or promote its qualities in various populations. The goal of the current meta-analysis is to substantiate existing evidence examining the promotion of resilience through various interventions. Particular emphasis was placed upon the factors that contribute to variability across interventions, such as age, gender, duration of intervention, intervention approaches and risk exposure of targeted population. Method: The literature search was conducted on May 28, 2019. Search terms included "resilience intervention" OR "promoting resilience" OR "promoting resiliency" OR "resilience-based intervention". A total of 268 studies, with 1584 independent samples, were included in the meta-analysis. In addition to overall efficacy, outcome-based analyses were conducted for intervention outcomes based on action, biophysical, coping, emotion, resilience, symptoms, and well-being. Finally, moderators of age, gender, length of intervention, intervention approach, intervention target, and the level of risk exposure of the sampled population were examined as moderators. Results: The multi-level meta-analysis indicated that resilience-promoting interventions yielded a small, but statistically significant overall effect, Hedges's g  = 0.48 ( SE  = 0.04, 95% CI  = [0.40, 0.56]. The variability in study effect sizes within and between studies was significant, p  < .001, with many falling short of the threshold for practical significance. Discussion: Findings lend some support for the overall efficacy of resilience interventions. However, empirical results should be cautiously interpreted in tandem with their theoretical relevance and potential advancements to the construct of resilience. Variabilities across findings reflect the current ambiguities surrounding the conceptualization and operationalization of resilience. Directions for future research on resilience as well as practical considerations are discussed. Highlights: There is no current consensus on operational definitions of resilience. Research continues to explore ways to enhance and/or promote resilience. Meta-analysis sought to substantiate evidence of resilience interventions. Findings lend some support for the overall efficacy of resilience interventions. Results should be cautiously interpreted alongside theoretical relevance. Variabilities in findings reflect ambiguities in resilience operationalization.